Sustainable supply chain management: a literature review of recent mathematical modelling approaches. Issue 4 (22nd August 2019) - Chanchaichujit, Janya; Pham, Quynh Chi; Tan, Albert
This research maps and defines the modelling approaches and mathematical techniques that have been used in solving supply chain problems in various industries. An analysis of peer-reviewed research papers has been conducted through a comprehensive search of the literature published from 2010 to 2016. Therefore, mathematical tools and techniques utilised in sustainable supply chain management research in each industrial sector will be identified, thereby opening up directions for future research. This paper addresses the shortfalls in previous works which have not yet addressed the application of mathematical modelling approaches with an industry focus. In addition, this paper also provides a reliable source of information for future expansion in sustainable supply chain management literature and the decision-making process in different industries.